THE EFFECT OF PENSION BENEFIT ON MILLENNIAL EMPLOYEES LOYALTY WITH PREFERENCE AND MOTIVATION AS MEDIATOR IN JAKARTA - Joko Purwanto, Tri; R. Sudiardhita, I Ketut; Rizan, Mohamad (Dinasti International Journal of Digital Business Management, 2021)
This study aims to determine and analyze the influence of Pension Benefit on millennial employees in Jakarta through preference and motivation as mediators. This research uses a qualitative and quantitative method using SEM Amos. The number of respondents were 262 that determined by purposive sampling technique. The result shows that: Pension Benefit has a significant positive effect to the employees loyalty; Pension Benefit has a significant positive effect to the employees preference; Pension Benefit has a significant positive effect to the employees motivation; employees preference has a significant positive effect to the employees loyalty; employees motivation has a significant positive effect to the employees loyalty; Pension Benefit hasn't a significant positive effect to the employees loyalty through employees preference; Pension Benefit hasn't a significant positive effect to the employees loyalty through employees motivation.